دراسة قياسية لسوق الكهرباء الجزائري: تحليل العرض والطلب على الكهرباء للفترة 2008 - 2015 - شناي، هاجر Shenai, Hajar; بن تفات، عبدالحق (جامعة محمد خيضر بسكرة - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2017)
في هذا البحث سوف نحاول تقديم دراسة قياسية في قطاع الطاقة الكهربائية في الجزائر إذ يعتبر هذا القطاع من القطاعات الاقتصادية المحركة لعجلة التنمية للبلاد لما تحظى به من أهمية ودور كبير في دفع عجلة الاقتصاد، وسوف نحاول من خلال هذه الدراسة وبالاعتماد على طريقة التحليل بالمكونات الرئيسيةACP Analyse en composantes principales متابعة المتغيرات الرئيسية لسوق الكهرباء في الجزائر وهما متغير عرض الكهرباء ممثلاً بإنتاج الكهرباء وكذلك متغير الطلب علي الكهرباء ممثلاً باستهلاك الكهرباء. من نتائج هذا البحث أن هناك فائض معتبر في إنتاج الكهرباء في الجزائر خلال كل السنوات المدروسة، كما أن هناك علاقة قوية جدا ً) تفوق (0.8 وموجبة أي طردية بين كل المتغيرات المدروسة وهي عرض الكهرباء، الطلب على الكهرباء، الفائض و/أو العجز في سوق الكهرباء، الناتج الداخلي الخام، تعداد السكان.
In this research paper we will try to provide an econometric study in the electric power sector in Algeria, as this sector of the economy the engine of the development wheel of the country because of its importance and the significant role in driving the economy, we will try through this study based on the (PCA Principal Component Analysis) follow-up the main variables of the electricity market in Algeria, which are the electricity supply represented by electricity production, as well as electricity demand variable represented by electricity consumption. One of the results of this research is that there is a significant surplus in the production of electricity in Algeria during all the years studied, and there is a very strong relationship (over 0.8), which is a positive one between all the variables studied : electricity supply, electricity demand, surplus and/or deficit in the electricity market, gross demestic product, population census.
Keywords: الطاقة الكهربائية -- إستهلاك الكهرباء -- التنمية الاقتصادية -- الجزائر